Isotopic signatures and patterns of volatile compounds for discrimination of genuine lemon, genuine lime and adulterated lime juices. (June 2022) - Jahani, Reza; van Ruth, Saskia; Yazdanpanah, Hassan; Faizi, Mehrdad; Shojaee AliAbadi, Mohammad Hossein; Mahboubi, Arash; Kobarfard, Farzad
Abstract: Isotopic signatures and patterns of volatile organic compounds (VOCs) are a useful set of markers for the authenticity assessment of fruit juices. In the present study, the carbon and nitrogen stable isotopes and VOCs fingerprinting of 16 genuine lemon and 16 genuine lime juices as well as 28 citric acid-adulterated lime juices were investigated to discriminate them and reveal the underlying mechanism for their differences. Samples were subjected to isotope ratio mass spectrometry (IRMS) and proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS). Following δ 13 C and δ 15 N analysis, no significant difference between genuine lemon (δ 13 C: -24.50 ± 1.29; δ 15 N: 5.40 ± 2.06) and genuine lime juices (δ 13 C: -25.17 ± 0.7; δ 15 N: 5.30 ± 0.97) was observed due to the same photosynthetic pathway (C3 photosynthetic pathway) of lemon and lime trees. However, Adulterated lime juice samples had higher δ 13 C values (-14.99 ± 2.79) and lower δ 15 N (1.23 ± 2.36) values compared to the genuine lemon and genuine lime juices which could be related to the added exogenous commercially available citric acid manufactured by fermenting sugars that follow the C4 photosynthetic pathway. Besides, a positive correlation (r 2 = 0.941) between citric acid to iso-citric acid ratios and δ 13 C values was found in the adulterated samples. No significant difference was observed in the total concentration of VOCs among the analyzed samples. However, for all samples, ions m/z 81 and 137 had the highest concentrations. Exploratory VOC pattern analysis by principal component analysis (PCA) and hierarchical cluster analysis (HCA) revealed the clustering of samples in different groups according to their nature. Besides, extremely adulterated samples were well distinguished from slightly adulterated samples following HCA analysis. The current study provided empirical evidence on the capability of IRMS and PTR-ToF-MS in the discrimination of lemon juice, lime juice, and adulterated lime juices. However, further investigation is required to confirm the promising results of this study. Highlights: IRMS and PTR-ToF-MS are able to detect citric acid-adulterated lime juices. PTR-ToF-MS analysis allows discrimination of lemon juice from lime juice. IRMS would not be a good choice for discrimination of lemon juice from lime juice. Adulterated lime juices show higher δ 13 C values compared to the genuine ones. There is a correlation between citric acid to iso-citric acid ratio and δ 13 C value.